Aspek Hukum Penanganan Masyarakat Terhadap Ancaman Air Limbah Ternak Babi (Studi Kasus Kelurahan Naibonat) - Humau, Winbert Julio; Pello, Jimmy; Fallo, Debby F Ng (Law Faculty, Nusa Cendana University, 2025)
Animal husbandry, while boosting community income and welfare, can lead to environmental pollution if livestock waste isn't properly managed. Untreated solid and liquid waste can cause public health problems and environmental damage, including risks of avian influenza, air and water pollution, and increased fly populations. Effective waste management is crucial for prevention. This research investigates the legal aspects of community security against the threat of pig wastewater in Naibonat Village and the real legal actions available to those affected. Employing empirical legal research, the study examines how the law functions within the community through data analysis and qualitative description. The findings reveal that despite legal efforts, no breeders in Kupang Regency have faced trial for environmental pollution due to the absence of criminal sanctions. This lack of legal consequences means there is no deterrent effect, allowing this harmful behavior and environmental damage to continue in the region.